Switzerland's Role as an International Financial Center - Christensen, Benedicte (Occasional Papers; Occasional Paper ;, 1986)
This paper was prepared by Benedicte Vibe Christensen in the European Department of the International Monetary Fund under the direction of Gyorgy Szapary. It describes developments in international financial transactions conducted through the Swiss banking system until December 1985.